Web-based parametric effort estimation for mobile application development / Nemo Menton Mufriz - Mufriz, Nemo Menton (2019)
Estimation methods are continuously adapted alongside this growth to obtain better and clearer estimations needed to achieve development goals. Some estimation methods were invented before the modern mobile application technology that is available now. Most probably these methods cannot cater for estimating modern mobile applications features. This study’s objectives are to identify parametric effort estimation techniques based on 25 mobile application development cost drivers and construct a web-based system to estimate the effort in developing mobile application. This study is adapted a mobile app estimation model and a systematic literature review from the previous research. The price range of the cost drivers are acquired from researching the available cots drivers from seven similar systems and calculated the mean value of the costs. The mean values are inserted into the new estimation metric using PHP and Javascript programming languages to produce the total estimation cost. The system is validated by comparing the results obtained with six similar systems according to basic user needs requirements in an application. This system is more enhanced cost estimation software that contains more cost driver options, which can be utilised by users to estimate mobile application development cost.